Gingival Health Status among the Arsenicosis Patients (City Dental College Journal, 2013)
Aims: The study was performed to assess gingival health status among the arsenicosis patients in comparison with the nonarsenicosis healthy individuals. Methods: A cross-sectional comparative type of study was conducted. One hundred and ninety two (192) arsenicosis patients and 96 non-arsenicosis healthy individuals were recruited purposively on the basis of defined selection criteria from January 2010 to June 2012. Research instrument was an interviewer questionnaire with gingival examination checklist. The questionnaire included socioeconomic family profile and the gingival checklist included attrition, pigmentation, gingivitis, and periodontitis. Results: One hundred and thirty seven (71.35%; n=137) of arsenicosis patients suffered from gingival attrition in comparison with the healthy individuals (38.54%; n=37). Gingival pigmentation was seen 61.98% (n=119) and 29.16% (n=28), respectively, among arsenicosis and non-arsenicosis individuals. Results also showed that 89.58% (n=172) of arsenicosis patients suffered from gingivitis, whereas, 44.79% (n=43) did not. In addition, 46.88% (n=90) and 25.00% (n=24) of arsenicosis and non-arsenicosis patients, respectively, were found suffered from periodontitis. Conclusion: Gingival health status of the arsenicosis patients was found relatively higher vulnerable to gingival attrition, pigmentation, gingivitis and periodontitis than that of nonarsenicosis healthy individuals. Health education intervention programs among the risk population and arsenicosis patients, and ensure of arsenic-free safe drinking and household use of water may be one of the most important applicable way to control and prevention of arsenicosis and gingival health problems in Bangladesh. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16316 City Dent. Coll. J Volume-10, Number-2, July-2013